2015
DOI: 10.5430/cns.v3n4p79
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of participation in shared governance to work satisfaction among cardiovascular nurses working in a tertiary hospital in Saudi Arabia

Abstract: Shared governance has been used as a framework that provides nurses with both the structure and the mechanism to enhance decision-making authority and improve level of satisfaction. This study examined the level of work satisfaction among nurses working at cardiovascular department after the implementation of Shared Governance Model in a tertiary hospital in the Kingdom of Saudi Arabia. A descriptive cross sectional study design was adopted using the Index of Work Satisfaction Part-B (IWS-Part-B). Non-random c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…In other words, more satisfied nurses were more motivated and appreciative of their work and found their work interesting. Similar results were obtained by Shwaihet and Nasaif (), who reported that participation in decision‐making and autonomy are strong predictors of job satisfaction. However, it should be noted that young RNs have also reported a lack of support, feelings of isolation and excessive responsibility as reasons for leaving the profession (Flinkman & Salanterä, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In other words, more satisfied nurses were more motivated and appreciative of their work and found their work interesting. Similar results were obtained by Shwaihet and Nasaif (), who reported that participation in decision‐making and autonomy are strong predictors of job satisfaction. However, it should be noted that young RNs have also reported a lack of support, feelings of isolation and excessive responsibility as reasons for leaving the profession (Flinkman & Salanterä, ).…”
Section: Discussionsupporting
confidence: 88%
“…Factors relating to nurses' working welfare such as professional development and competence are enhanced by autonomy and decision‐making. Satisfaction with job status (full‐time or part‐time), work‐life balance and access to resources (support staff) are important factors for retaining nurses in the profession (Tourangeau et al, ), while shared governance strategies encourage nurses to play more active roles in decision‐making (Shwaihet & Nasaif, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the autonomy nurses had in their work and the extent of their interactions with other nurses and physicians have also been reported to play a significant role in their job satisfaction. [27] Lastly, the total years of experience working in their current units had also a significant relationship with their level of job satisfaction. Nurses who had worked between 16 to 20 years in their current unit had the highest level of satisfaction, while nurses with 10 to 15 years of experience in their current unit had the lowest level.…”
Section: Increased Job Satisfactionmentioning
confidence: 97%
“…The autonomous participation in decision-making processes contributes to frontline staff to achieve job satisfaction. [25][26][27] Engagement in decision-making offered nurses a sense of having control over their practice and having a voice in their patients' care planning. Further, the autonomy nurses had in their work and the extent of their interactions with other nurses and physicians have also been reported to play a significant role in their job satisfaction.…”
Section: Increased Job Satisfactionmentioning
confidence: 99%